2016
DOI: 10.1155/2016/9392132
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role and Therapeutic Implication of Wnt Signaling Pathways in Autoimmune Diseases

Abstract: The Wnt signaling pathway plays a key role in many biological aspects, such as cellular proliferation, tissue regeneration, embryonic development, and other systemic effects. Under a physiological condition, it is tightly controlled at different layers and arrays, and a dysregulated activation of this signaling has been implicated into the pathogenesis of various human disorders, including autoimmune diseases. Despite the fact that therapeutic interventions are available for ameliorating disease manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 148 publications
4
86
0
4
Order By: Relevance
“…41 Dysregulation of the Wnt/beta-catenin signalling pathway may alternate regulatory T cell function and it has been suggested as a potential novel therapeutic target in autoimmune disorders. 42 Interestingly, PRICKLE1 has been identified as a GD risk locus in the Immunochip study, 32 and we showed that the PRICKLE1 risk variant was nominally more frequent in POGD comparing to AOGD patients in our study and it might be associated with age of GD onset.…”
Section: Other Genes Potentially Associated With Age Of Gd Onsetsupporting
confidence: 49%
See 1 more Smart Citation
“…41 Dysregulation of the Wnt/beta-catenin signalling pathway may alternate regulatory T cell function and it has been suggested as a potential novel therapeutic target in autoimmune disorders. 42 Interestingly, PRICKLE1 has been identified as a GD risk locus in the Immunochip study, 32 and we showed that the PRICKLE1 risk variant was nominally more frequent in POGD comparing to AOGD patients in our study and it might be associated with age of GD onset.…”
Section: Other Genes Potentially Associated With Age Of Gd Onsetsupporting
confidence: 49%
“…While initially associated with planar cell polarity, the PRICKLE1 gene encodes a nuclear receptor acting as a negative regulator of the Wnt/beta‐catenin signalling pathway, which, among others, plays also a crucial role in T cell development and differentiation . Dysregulation of the Wnt/beta‐catenin signalling pathway may alternate regulatory T cell function and it has been suggested as a potential novel therapeutic target in autoimmune disorders . Interestingly, PRICKLE1 has been identified as a GD risk locus in the Immunochip study, and we showed that the PRICKLE1 risk variant was nominally more frequent in POGD comparing to AOGD patients in our study and it might be associated with age of GD onset.…”
Section: Discussionmentioning
confidence: 74%
“…Wnt proteins are members of a family secreted molecules, which bind to their seven-pass transmembrane Frizzled (FZD) receptors and result in the activation of the central player of the pathway, β-catenin at downstream (Gruber, Yee, & Tolwinski, 2016). This signaling plays a substantial function in cell proliferation, differentiation, growth, survival, development, regeneration, self-renewal, and cell fate determination (Shi et al, 2016). Because It regulates a broad range of the cell-fate decisions related to osteogenesis, Wnt signaling has been suggested to be involved throughout the healing process (Krishnan, Bryant, & MacDougald, 2006).…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…Wnt, as a large family of ligands, for membranespooning frizzled (FZD) receptors, is involved in proliferation, growth, migration, polarity, differentiation, and cell death (40,41 …”
Section: Effect Of Wnt Active Wnt/β Catenin Signaling Pathway On Ostementioning
confidence: 99%